2016
DOI: 10.1007/s13278-016-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of reciprocal recommendation systems for online dating

Abstract: Online dating sites have become popular platforms for people to look for potential romantic partners. Different from traditional user-item recommendations where the goal is to match items (e.g., books, videos) with a user's interests, a recommendation system for online dating aims to match people who are mutually interested in and likely to communicate with each other. We introduce similarity measures that capture the unique features and characteristics of the online dating network, for example, the interest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Male served as the reference category for gender to which females would be compared for the models predicting sex without a condom and concurrent sex partners. Previous research suggested that men tend to be more assertive regarding online dating (Xia et al 2016). Therefore, for the model that predicted pursuing Bhookupsv ia Facebook, female served as the reference category to which male gender would be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Male served as the reference category for gender to which females would be compared for the models predicting sex without a condom and concurrent sex partners. Previous research suggested that men tend to be more assertive regarding online dating (Xia et al 2016). Therefore, for the model that predicted pursuing Bhookupsv ia Facebook, female served as the reference category to which male gender would be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal relationships are also explored in Bipartite social network of online dating for providing date partner recommendations (Zhao et al , 2014; Xia et al , 2016). Recently, a very interesting issue of understanding and predicting delay in reciprocal relations is investigated (Li et al , 2017).…”
Section: Related Workmentioning
confidence: 99%
“…As a special type of social networking sites [1][2][3], online dating sites have emerged as popular platforms for single people to seek potential romance. According to a recent survey, nearly 40 million single people (out of 54 million) in the U.S. have been trying online dating, and about 20% of committed relationships began online [4]. Although some psychologists have questioned the reliability and effectiveness of online dating [5], recent empirical studies using the tracking data and survival analysis found that for heterosexual couples, meeting partners through online dating sites can speed up marriage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Computer scientists usually study online dating from the perspective of user behaviors [39][40][41] and recommendation systems [4,[42][43][44]. By analyzing online dating data, Xia et al found that there exists distinct difference between preferences of men and women [41], and there also exists difference between users' stated and actual preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation